2021
DOI: 10.3390/ijms22042004
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Role of Wnt and Rho Signaling Pathway in iPSC-Derived ARVC Cardiomyocytes by In Silico Mathematical Modeling

Abstract: Arrhythmogenic Right Ventricular cardiomyopathy (ARVC) is an inherited cardiac muscle disease linked to genetic deficiency in components of the desmosomes. The disease is characterized by progressive fibro-fatty replacement of the right ventricle, which acts as a substrate for arrhythmias and sudden cardiac death. The molecular mechanisms underpinning ARVC are largely unknown. Here we propose a mathematical model for investigating the molecular dynamics underlying heart remodeling and the loss of cardiac myocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 45 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…In corneal epithelial cells, inhibition of ROCK led to a translocation of E-Cadherin to the cytoplasm (Anderson et al, 2002). Apart from that, using an in silico mathematical model, it has been suggested that ROCK plays a role in the pathogenesis of AC (Parrotta et al, 2021). Furthermore, inhibition of ROCK during early cardiac development did lead to AC in a murine model with a reduced localization of PG at the ICD (Ellawindy et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In corneal epithelial cells, inhibition of ROCK led to a translocation of E-Cadherin to the cytoplasm (Anderson et al, 2002). Apart from that, using an in silico mathematical model, it has been suggested that ROCK plays a role in the pathogenesis of AC (Parrotta et al, 2021). Furthermore, inhibition of ROCK during early cardiac development did lead to AC in a murine model with a reduced localization of PG at the ICD (Ellawindy et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In corneal epithelial cells, inhibition of ROCK led to a translocation of E-Cadherin to the cytoplasm (Anderson et al, 2002). Apart from that, using an in silico mathematical model, it has been suggested that ROCK plays a role in the pathogenesis of AC (Parrotta et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In embryonic heart, ROCK inhibition could lead to fibrofatty replacement of cardiomyocytes in the right ventricle of adult mice resulting in arrhythmogenic right ventricular cardiomyopathy ( 165 ). Mechanistically, both Wnt/β-catenin and RhoA/ROCK pathways must be inactive for a significant increase of PPARγ expression, which is responsible for mediating arrhythmogenic right ventricular cardiomyopathy pathogenesis ( 166 ). Moreover, in embryonic heart, the RhoA/ROCK/F-actin/MRTF-A/SRF pathway is essential to maintaining cell-cell contacts of developing cardiomyocytes and inhibiting this pathway during cardiomyocyte differentiation primes cardiac progenitors to switch to the brown/beige adipocyte lineage in response to adipogenesis-inducing signals ( 114 ).…”
Section: Cellular Actions Of Rock Signaling Pathways In Adipose Tissuementioning
confidence: 99%
“…In corneal epithelial cells, inhibition of ROCK led to a translocation of E-Cadherin to the cytoplasm (68). Apart from that, using an in silico model, it has been suggested that ROCK plays a role in the pathogenesis of AC (69).…”
Section: Discussionmentioning
confidence: 99%